PERSPECTIVES OF REGIONAL LABOR INTEGRATION IN MERCOSUR TOWARDS REVISIONS IN PROTECTING DECENT LABOR - Martins, Juliane Caravieri (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2019)
Regional integration in MERCOSUR can no longer be limited to trade issues, but must include labor issues in order to reduce the asymmetries of economic development. The aim of this research is to demonstrate that the return of the conservative right in mercosurist countries is driving the dismantling of labor rights, making it impossible to continue the social agenda in the bloc that was driven by postliberal regionalism. The factors that involve the issue of wage labor in Latin America are complex, requiring the “spillover” of economic development to social areas, especially involving human labor and worker migration. If MERCOSUR does not prioritize labor relations, the integrationist project will not be fully implemented and may fade in the coming decades.